2015
DOI: 10.1186/s13045-015-0143-3
|View full text |Cite
|
Sign up to set email alerts
|

Azacytidine sensitizes acute myeloid leukemia cells to arsenic trioxide by up-regulating the arsenic transporter aquaglyceroporin 9

Abstract: BackgroundThe therapeutic efficacy of arsenic trioxide (As2O3) in acute myeloid leukemia (AML) is modest, which is partly related to its limited intracellular uptake into the leukemic cells. As2O3 enters cells via the transmembrane protein aquaglyceroporin 9 (AQP9). Azacytidine, a demethylating agent that is approved for the treatment of AML, has been shown to have synergistic effect with As2O3. We tested the hypothesis that azacytidine might up-regulate AQP9 and enhances As2O3-mediated cytotoxicity in AML.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 30 publications
2
22
0
Order By: Relevance
“…In this study, we used a concentration of ATO (6 μ M) to construct an in vitro liver cell injury model. A relative high concentration of ATO in anti-blood tumor researches is 6 μ M, 40 , 41 but commonly used in solid tumor researches. 42 , 43 , 44 By in vitro and in vivo assays, we demonstrated the protective effects of metformin on ATO-induced liver injury.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we used a concentration of ATO (6 μ M) to construct an in vitro liver cell injury model. A relative high concentration of ATO in anti-blood tumor researches is 6 μ M, 40 , 41 but commonly used in solid tumor researches. 42 , 43 , 44 By in vitro and in vivo assays, we demonstrated the protective effects of metformin on ATO-induced liver injury.…”
Section: Discussionmentioning
confidence: 99%
“… 30 , 31 In some recent studies, AZT exhibited significant synergistic therapeutic with other drugs for tumors in a safe dosage range. 32 34 Chau et al 35 suggested that the combination of azacytidine with As 2 O 3 would be a logical drug combination for treatment of AML in the future. Wang et al 36 reported that the combination of AZT with emodin could co-inhibit the proliferation of leukemia KG-1a cells.…”
Section: Discussionmentioning
confidence: 99%
“…As indicated in lung cancer and glioma, BSO was shown to enhance the ATOinduced anticancer effect by mediating ROS generation in AML cells [87] and other leukemic/lymphoma cells [88], suggesting that combined ATO-BSO treatment would be one of the attractive alternative therapies for cancer treatment. It has also been reported that combined treatment with ATO and dichloroacetate [89], azacytidine [90], rapamycin [91], and aclacino-…”
Section: Acute Myeloid Leukemia (Aml)mentioning
confidence: 95%